Determination of Kinetic and Thermodynamic Parameters of Pb(II) Ion Adsorption Using Dithizone-Immobilized Coal Fly Ash - Muh Rizal B.; Mudasir Mudasir; Dwi Siswanta; Melvi Muharmi; Vebria Ardina; Teguh Setyawan; Nur Jaya; Defia Indah Permatasari; Revi Maylina Tanjung (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
The immobilization of dithizone on the surface of coal fly ash was successfully achieved, as evidenced by Fourier-transform infrared (FT-IR) and X-ray diffraction (XRD) characterization. The dithizone-immobilized coal fly ash (CFA-Dzt) was then used for Pb(II) ion adsorption. The parameters studied included the effects of pH, kinetics, and thermodynamics on Pb(II) ion adsorption using a batch experimental system. The results showed that the optimum pH for Pb(II) adsorption using CFA-Dzt was 5. The adsorption kinetics of Pb(II) ions followed the pseudo-second-order kinetic model, with an adsorption activation energy of 27.280 kJ mol−1. The Langmuir isotherm model best described the adsorption behavior, with a maximum adsorption capacity of 34.13 mg g−1. Thermodynamic analysis revealed Gibbs free energy changes (ΔG°) of 24.630, 25.850, 26.810, and 28.550 kJ mol−1 at 293, 303, 313, and 323 K, respectively. The enthalpy change (ΔH°) of the adsorption at this temperature range was +12.770 kJ mol−1, indicating that Pb(II) ion adsorption on the adsorbent is an endothermic process, and its entropy change (ΔS°) was +127.290 J mol−1, suggesting that the adsorption of Pb(II) ion on CFA-Dzt is dominantly driven by the entropic factor.